Analisis Konsep Dasar dan Landasan Hukum Pasar Modal Syariah di Indonesia - Maryam Batubara; Ahyarul Juanda Sagala; Abdillah Abdillah; Fazlurrasyid Sulaiman Martua Siregar; Farhan Syafiq (Lembaga Pengembangan Kinerja Dosen, 2025)
This study uses a qualitative method with a descriptive approach to describe the principles, functions, and financing analysis at Bank Syariah Indonesia (BSI) as a financial institution that applies sharia principles in its operations. The main focus of this study is to explain how sharia principles such as justice, partnership, and prohibition of usury are implemented in financing practices and how sharia banks function not only as financial intermediaries, but also as development and social agents. Financing carried out by BSI is studied through types of products such as murabahah, musyarakah, and mudharabah, each of which is analyzed in terms of contracts, risks, and their contribution to the economic growth of the community. Data were obtained through literature studies and documentation from official BSI reports and related scientific publications. The results show that the application of sharia principles in financing provides a fair and transparent alternative compared to conventional systems, and is able to encourage financial inclusion and community economic empowerment. Thus, sharia financing at BSI not only fulfills commercial aspects, but also spiritual and social aspects.